The Flavin-Containing Monooxygenase 3 Gene and Essential Hypertension: The Joint Effect of Polymorphism E158K and Cigarette Smoking on Disease Susceptibility - Olga Bushueva; Maria Solodilova; Mikhail Churnosov; Vladimir Ivanov; Alexey Polonikov (International Journal of Hypertension)
Gene encoding flavin-containing monooxygenase 3 (FMO3), a microsomal antioxidant defense enzyme, has been suggested to contribute to essential hypertension (EH). The present study was designed to investigate whether common functional polymorphism E158K (rs2266782) of the FMO3 gene is associated with EH susceptibility in a Russian population. A total of 2 995 unrelated subjects from Kursk (1 362 EH patients and 843 healthy controls) and Belgorod (357 EH patients and 422 population controls) regions of Central Russia were recruited for this study. DNA samples from all study participants were genotyped for the FMO3 gene polymorphism through PCR followed by RFLP analysis. We found that the polymorphism E158K is associated with increased risk of essential hypertension in both discovery population from Kursk region (OR 1.36 95% CI 1.09–1.69, P=0.01) and replication population from Belgorod region (OR 1.54 95% CI 1.07–1.89, P=0.02) after adjustment for gender and age using logistic regression analysis. Further analysis showed that the increased hypertension risk in carriers of genotype 158KK gene occurred in cigarette smokers, whereas nonsmoker carriers of this genotype did not show the disease risk. This is the first study reporting the association of the FMO3 gene polymorphism and the risk of essential hypertension.